Competitiveness and Economical Expansion of Industry - Valentinavičius, Stasys (Ekonomika, 2000)
The article analyses the importance of industry far the country economy; it’s expansion tendencies in the world. Methodological problems of firm’s competitiveness evaluation are discussed in this article as well. Research results of valuation of the competitiveness of most important Lithuanian industry branches, based on the productivity index in 1996-1998, are presented in the paper. Suggestions far increase are highlighted here as well.